Men in communal roles. The influence of gender incongruent role models on gender stereotypes and occupational aspirations of kindergarten children in Northern Norway - Ofori, George Kwadwo (UiT Norges arktiske universitet, 2018)
Research in the past has looked extensively at gender segregation in the workforce, where men and women are “divided” into bigger domains of work based on traditional gender roles attributed to them (Watt, 2008; Tellhed, Bäckström & Björklund, 2016). These two domains are STEM: science, technology, engineering, and mathematics (Beede et al., 2011) and HEED: healthcare, elementary education, and domestic functions (Croft et al., 2015). Where many studies have examined the difficulties experienced by women participating in the STEM or agentic professions, a much lower amount of research focuses on the barriers men face when entering HEED or communal roles (Croft et al., 2016). In order to further understand how gender disparity in labour develops, we turned to Norwegian kindergartens. This study investigated whether children (78 boys, 71 girls; Mage = 66.6 months, range = 54-83 months) who attended kindergartens with both male and female staff held more gender egalitarian views and aspirations than those who attended kindergartens with female staff only. We also looked at the roles that male kindergarten teachers play as role models. In reporting gender stereotypes of occupations, there were no significant preferences for either communal or agentic occupations as the children mainly reported that both genders could work in most occupations. Moderational analyses showed no significant effect of the gender of the kindergarten teachers on the children’s stereotypes, but there was a significant relationship between the boys’ internalised traits and willingness to work in communal occupations. These results are discussed in light of the Norwegian Action Plan aiming to increase the number of male kindergarten teachers in Norway.